Strategi Guru Bimbingan Konseling dalam Eksplorasi dan Pengambilan Keputusan Karier pada Siswa di Kabupaten Barru - Andi Jaya Alam Passalowongi; Fiptar Abdi Alam; Taufik Taufik (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
This study discusses the strategies implemented by Guidance and Counseling (GC) teachers in assisting students to explore and determine their career choices. The study employs a qualitative approach with a descriptive method. Data were collected through in-depth interviews, observations, and document analysis conducted at Madrasah Aliyah Muhammadiyah Padaelo, Barru Regency. Based on the research findings, it can be concluded that the implementation of career guidance at this school has been running fairly well, although it still faces several challenges. GC teachers serve as the main facilitators in providing information, direction, and motivation to students regarding career choices that align with their interests, talents, and potential. Support from homeroom teachers and the school principal also contributes to the continuity of this program, although coordination among stakeholders still needs to be improved. The approaches used—such as group discussions, individual counseling, and the involvement of external parties—have proven effective in broadening students’ perspectives. However, limitations in facilities, time, and resources pose significant obstacles to the implementation process. With these efforts, it is hoped that career guidance in schools can become more optimal, relevant, and have a long-term impact on students' futures.